Correlation between Farmers' Activeness in Farmer Groups with Productivity and Income of Cocoa Farming in Trenggalek Regency - Hariyati, Yuli; Ria, Vina Yunita; Rahman, Rena Yunita; Ibanah, Indah; Rosyady, Muhammad Ghufron (Food, Agriculture and Natural Resources - NETWORKS, 2024)
The cocoa plantation in Suruh Village, Trenggalek Regency is the main supplier of cocoa beans to UPH Rumah Coklat owned by the Department of Agriculture and Food of Trenggalek Regency. For example, in cocoa farmers' participation in the